DOMESTIC AND FOREIGN EXPERIENCE OF EDUCATIONAL AND METHODICAL ENSURING QUALITY OF TRAINING OF FUTURE EXPERTS (on the example of Al-Farabi KazNU and the Erzincan university Binali Yildirim) (Journal of Educational Sciences, 2019)
Questions of quality of training of social teachers remain in the center of attention of scientific research and practice of management of education, as from a year – a year of the quantity of grants, on this specialty grows, demand for competent social teachers grows in regions, control from the state amplifies and employers also the volume of problems with which social teachers face and work increases. Moreover, innovative processes in education, at any approach to their assessment, regard a problem either maintaining the existing level of quality of education, or achievement of higher level as of paramount importance.The purpose of this article is to give a comparative review of the features and content of the teaching and methodological support of the quality of education at universities in Turkey and Kazakhstan. The main research methods are theoretical methods of analysis, systematization, and generalization. In general, the comparative review presents empirical material are collected during a scientific internship at the Binali Yildirim University in Erzindzhan at the Faculty of Education. Significance: the results of the study can be useful for managers and managers of the education system, for university teachers to adjust the content and technologies of training future specialists.Keywords: quality of training, educational and methodical providing, curriculum, syllabus, textbook